Multifaceted Development and Reduction of Social Inequalities: The Access of Blacks and Blinds to Public Higher Education (Research, Society and Development, 2020)
Seeking to disconnect the reductionist notion of development from the bias of economic progress, the present work aims to explore, in an interdisciplinary way, how development, established as a complex phenomenon with several facets, can be recognized as a scientific basis to support public policies of ethnic-racial quotas. Thus, by inserting the individual at the center of the issue under focus, we will analyze development as a tool for the emancipation of blacks (blacks and browns), highlighting the role of the State and non-governmental actors in the process of formatting and maintaining compensatory public policies remedies, leveraged by access to public higher education. In this context, we will be able to uncover ways to reduce social inequalities in this historically discriminated segment, concluding that the interaction between blacks, browns and whites within universities reinforces cultural diversity and democracy in Brazil, contributing to the formation of better prepared leaders and connoisseurs of national identity.